Chlamydial Lower Genital Tract Infection and Spontaneous Abortion - J. Sozio; R. B. Ness (Hindawi Limited, 1998)
Objective: Few previous studies have examined the role that acute Chlamydia trachomatis lower genital tract infection plays in the development of spontaneous abortion. This study evaluated cervical C. trachomatis infections among 52 women experiencing spontaneous abortion and 59 controls.